Using peer-support to connect learning network participants to each other: an interdisciplinary approach. (1st January 2012) - Fetter, Sibren; Berlanga, Adriana J.; Sloep, Peter; van der Vegt, Wim; Rajagopal, Kamakshi; Brouns, Francis
A large-scale experiment is presented which examines the feasibility of using a new method of peer-support called ad hoc transient groups (AHTGs) to foster social capital of learning network participants. In AHTGs participants that have a request are helped by other participants in a dedicated private space ('ad-hoc') which exists for a limited amount of time only ('transience'). To test the hypotheses that AHTGs foster social capital, AHTGs were introduced to a subset of the eTwinning learning network (+130.000 teachers). To validate the results, a No-intervention group and a comparison group that used a forum to ask questions instead of AHTGs were also examined. Results show that AHTGs seem to foster social capital on the level of relationship characteristics and mutual support. Results on sense of connectedness were inconclusive. It is concluded that AHTGs have a decentralising effect, making the network less dependent on a few key participants. Furthermore, AHTGs have clearly been shown to have a low threshold to ask a question. Within the Forum group only a few core participants asked questions, yet many participants replied. It is concluded that AHTGs foster social capital in a different way when compared to a forum.